2016
DOI: 10.1097/phh.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Multisector Health Policy Networks in 15 Large US Cities

Abstract: Supplemental Digital Content is Available in the Text.This study describes a network approach to examine local health department partnerships across large cities from the Big Cities Health Coalition in health policy areas such as core local funding, tobacco control, obesity and chronic disease, violence and injury prevention, and infant mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A recent review on information sharing in a health care provider setting also showed transitivity to be an important factor (Bae et al, 2015). Additionally, the impact of transitive collaborations were also reported in multisector health policy networks (Harris et al, 2016) and sport tourism cooperation (W€ asche, 2015). In a study on governmental collaborations, researchers suggested transitivity could be a sign of asymmetrical collaborations between more active members and relatively less active members which may also be the case in this network (Ulibarri and Scott, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…A recent review on information sharing in a health care provider setting also showed transitivity to be an important factor (Bae et al, 2015). Additionally, the impact of transitive collaborations were also reported in multisector health policy networks (Harris et al, 2016) and sport tourism cooperation (W€ asche, 2015). In a study on governmental collaborations, researchers suggested transitivity could be a sign of asymmetrical collaborations between more active members and relatively less active members which may also be the case in this network (Ulibarri and Scott, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Examples of this are illustrated in the development and implementation of Community Health Improvement Plans, chronic disease management, environmental health issues, and many other public health issues. LHDs need to be able to create change in systems and communities through collaborations that regularly engage partners at different levels and across different sectors [17,18]. This would allow all to become more aware of factors that influence community health and well-being and the interconnected nature of public health.…”
Section: Discussionmentioning
confidence: 99%
“…Additional details on data collection are available elsewhere. 41 The Washington University in St Louis Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…From these sources, we compiled a full list of policy partners for each of the 15 jurisdictions. Descriptive statistics quantifying network size (ie, number of network members including the LHD and its policy partners), density, degree centralization (ie, the extent to which a network includes a single member or a small number of members with more ties than the others), and composition (ie, how many types of partners are in each network) of the networks in all 5 areas are compared elsewhere 41 ; this study focused on the composition and structure of the IVP networks.…”
Section: Participantsmentioning
confidence: 99%